2018
DOI: 10.1002/jso.25058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sentinel lymph node biopsy guided by blue dye with or without indocyanine green in early breast cancer

Abstract: The combined method achieved a higher identification rate and lower rate of axillary recurrence compared to the blue dye alone method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 13 publications
2
35
1
Order By: Relevance
“…ICG, a novel technique for SLNB, is increasingly used in clinical practice. The SLNB detection rate with ICG alone ranges from 93.1 to 100%, for 1.5-5.4 sentinel lymph nodes sampled per patient [5, 6, 11, 1618, 20, 21]. The combined use of the conventional blue dye with ICG fluorescence could improve SLN localization and potentially reduce surgical time [2224].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG, a novel technique for SLNB, is increasingly used in clinical practice. The SLNB detection rate with ICG alone ranges from 93.1 to 100%, for 1.5-5.4 sentinel lymph nodes sampled per patient [5, 6, 11, 1618, 20, 21]. The combined use of the conventional blue dye with ICG fluorescence could improve SLN localization and potentially reduce surgical time [2224].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new techniques are being developed for SLNB. Among them, indocyanine green fluorescence (ICG) and contrast-enhanced ultrasound (CEUS) have some advantages [5, 6, 921]. Recent studies confirmed that ICG or CEUS alone is feasible and safe for SLNB.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is a shift in practice toward the use of ICG, a fluorescent dye as an optical tracer. ICG does not stain the injection site under white light and the fluorescent signal can penetrate through overlying soft tissue (typically to a maximum of 1 cm, which can be increased by compression of overlying tissue), facilitating the intraoperative localization of the SN . There is a requirement for a near‐infrared camera to visualize the fluorescent dye during surgery.…”
Section: Recommendationsmentioning
confidence: 99%
“…ICG requires the near-infrared light source of the fluorescent vascular imaging system to be excited in real time, and the imaging device is used to observe the subcutaneous lymphatic drainage pathway to mark the SLN. 21 Superparamagnetic iron oxide is represented by mononuclear macrophages in the lymphatic system. Through the action of an external magnetic field, iron oxide produces magnetism to achieve its tracking effect.…”
Section: Discussionmentioning
confidence: 99%